3 x 2 − 2 x − 5 = 2 7
Given that x 1 and x 2 are the real solutions to this equation and that x 1 > x 2 , find ln x 1 ln ∣ x 2 ∣
Notation: ∣ ⋅ ∣ denotes the absolute value function
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We know that 2 7 = 3 3 : 3 x 2 − 2 x − 5 = 2 7 ⟹ 3 x 2 − 2 x − 5 = 3 3 Since the bases are the same, we can deduce that the exponents must be the same: ⟹ x 2 − 2 x − 5 = 3 subtract 3 x 2 − 2 x − 8 = 0 factorise ( x + 2 ) ( x − 4 ) = 0 We can see that our solutions for x are 4 and − 2 and since 4 > − 2 we can say that x 1 = 4 and x 2 = − 2 . Now, we can work out the answer: ln x 1 ln ∣ x 2 ∣ = ln 4 ln ∣ − 2 ∣ = 2 ln 2 ln 2 = 2 1
Problem Loading...
Note Loading...
Set Loading...
3 x 2 − 2 x − 5 = 2 7 = 3 3
⟹ x 2 − 2 x − 5 = 3
⟹ x = { − 2 , 4 }
⟹ x 1 = 4 , ∣ x 2 ∣ = 2
ln x 1 ln ∣ x 2 ∣ = ln 4 ln 2 = lo g 4 2 = 0 . 5